Patient-reported tolerability and acceptability of cabotegravir + rilpivirine long-acting injections for the treatment of HIV-1 infection: 96-week results from the randomized LATTE-2 study - Miranda Murray; Federico Pulido; Anthony Mills; Moti Ramgopal; Roger LeBlanc; Hans Jaeger; Viviam Canon; David Dorey; Sandy Griffith; Joseph Mrus; William Spreen; David Margolis (HIV Research & Clinical Practice, 2019)
Background: Long-acting (LA) injectable antiretroviral therapy (ART) is a novel modality currently under development as an alternative to daily oral ART. Objective: The LATTE-2 study (ClinicalTrials.gov identifier NCT02120352) showed that cabotegravir LA + rilpivirine LA maintained virologic suppression through 96 weeks and included further exploration of patient-reported treatment outcomes with an LA injectable form of treatment. Methods: Two-hundred and eighty-six virologically suppressed participants on oral cabotegravir + abacavir/lamivudine once-daily tablets (induction period) were randomized to cabotegravir LA + rilpivirine LA once every 4 weeks (n = 115), once every 8 weeks (n = 115), or the continuation of the oral tablet regimen (n = 56) during the maintenance period. Patient-reported outcome measures included the HIV Medications Questionnaire (HIVMQ) and the HIV Treatment Satisfaction Questionnaire status (HIVTSQ[s]) and change (HIVTSQ[c]) versions at prespecified study visits through Week 96 of the randomized maintenance period. Results: Most participants in the LA injectable groups reported injection-site–related adverse events; however, participants in the 4-week (median HIVTSQ[s] total score, 63.5; post hoc P = 0.02) and 8-week (65.0; post hoc P < 0.001) LA injectable groups were significantly more satisfied with treatment than participants in the oral maintenance group (60.0) at Week 96. This was consistent with results from the HIVTSQ[c] at Week 32, which revealed that participants in both LA groups were significantly more satisfied with therapy compared with patients receiving oral ART (both post hoc P < 0.001). Conclusion: Participants who received LA injectable therapy had high levels of treatment satisfaction and favorably viewed convenience and lifestyle-related aspects of the therapy.